Numerical simulation of gas-solid flow characteristic of particles in fibrous media using OpenFOAM. Issue 7 (August 2020) - Shu, Zhiyong; Qian, Fuping; Zhu, Jinjing; Lu, Jinli
Euler-Lagrangian numerical simulation framework of gas-solid two-phase flow was used to simulate the gas-solid flow characteristic in fibrous media using OpenFOAM in this study. The simulation results were compared with the empirical model and CFD-DEM method. In addition, the deposition morphology of particles, pressure differential and filtration efficiency in unsteady stage and simulation cost were also analysed with OpenFOAM. The results show that OpenFOAM can simulate the process of gas-solid two-phase flow in the fibrous media, and the particles are agglomerated on the surface of fibrous media and form a dendritic structure similar to the experimental observation. The pressure differential in unsteady stage would increase with the mass per unit area. The filtration efficiency would increase with a corresponding increase in the amount of deposition, but the growth rate would decline gradually. Compared with CFD-DEM method, the simulation accuracy with OpenFOAM is slightly lower, especially in the case of large the Stokes number, but the simulation cost is low, too. Therefore, it is necessary to choose one of the two methods according to the actual situation.